Economic Journalism and the Elitist Approach - Raul Rios-Rodríguez; Ángel Arrese (Brazilian Journalism Research, 2021)
ABSTRACT – Is economic journalism always dependent on elitist news sources or are there particular situations that can mitigate this pattern? The economic crisis of 2008 has specific characteristics that distinguish it from the issues usually covered by economic journalism, so a different pattern in the use of sources could be expected, especially if we consider the changing economic and political circumstances throughout the crisis. To explore this question, we conducted a content analysis of the crisis coverage of representative Spanish newspapers between 2008 and 2015. The results show that the political and economic elites were the dominant sources, meanwhile, other non-elite agents had little presence. This imbalance is not modified by the ideological and geographical profiles of the newspapers, or by the different phases of the crisis. However, we found intra-elite alterations over time: the actors with more decision-making power at each period had more presence as sources.